2019
DOI: 10.3390/insects10040095
|View full text |Cite
|
Sign up to set email alerts
|

Residual Efficacy of a Deltamethrin Emulsifiable Concentrate Formulation against Rhyzopertha dominica (F.) and Sitotroga cerealella (Oliver) after Partial Treatment of Brown Rice

Abstract: Rhyzopertha dominica (Fab.), the lesser grain borer, and Sitotroga cerealella (Olivier), the Angoumois grain moth, are internally feeding stored product insects that can infest raw grains. In this test, brown rice was treated with 0.5 and 1.0 ppm of a new emulsifiable concentrate (EC) formulation of the pyrethroid deltamethrin and stored for 12 months. One day after treatment, and every 3 months for 12 months, treated rice was mixed with untreated brown rice in the following ratios: 0:100 (untreated controls),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Partial commodity treatment, top-dressing treatment in particular, is inherently associated with a varying risk of incomplete efficacy. As noted by Arthur [ 566 ], both dust and spray top-dressing may offer insects ample opportunities to penetrate through the treated surface into the untreated portion of the grain. Vardeman et al [ 567 ], in a study with diatomaceous earth (DE), reported that stored-product insects may penetrate through a dust-treated surface in a grain mass in a physiological state that enables them to oviposit in the untreated layers before they die.…”
Section: Insecticide Delivery In Solid Formsmentioning
confidence: 99%
“…Partial commodity treatment, top-dressing treatment in particular, is inherently associated with a varying risk of incomplete efficacy. As noted by Arthur [ 566 ], both dust and spray top-dressing may offer insects ample opportunities to penetrate through the treated surface into the untreated portion of the grain. Vardeman et al [ 567 ], in a study with diatomaceous earth (DE), reported that stored-product insects may penetrate through a dust-treated surface in a grain mass in a physiological state that enables them to oviposit in the untreated layers before they die.…”
Section: Insecticide Delivery In Solid Formsmentioning
confidence: 99%
“…Historical data and recent research show that Sitophilus oryzae (L.), the rice weevil, is much more tolerant to pyrethroids used as contact insecticides on stored grains and on treated surfaces, compared to Rhyzopertha dominica (F.), the lesser grain borer [7,8]. Nonetheless, recent research shows that a combination of methoprene with the pyrethroid deltamethrin may still give enhanced control of S. oryzae [9]. The current commercial formulation of deltamethrin plus methoprene used in the United States (US) is Diacon IGR+ ® (Central Life Sciences, Schaumberg, IL, USA).…”
Section: Introductionmentioning
confidence: 99%
“…For each exposure interval and RH level, within each dose, means followed by the same uppercase letter are not significantly different; df = 2, 26, Tukey-Kramer (HSD) test at P = 0.05. Where no letters exist, no significant differences were recorded 46.7 ± 5.5 Aab 26.1 ± 5.9 Bb 41.7 ± 2.9 Ab 3.9 0.04 30.0 ± 3.5 bc 28.3 ± 6.5 bc 23.9 ± 4.3 bc 0.5 0.61 5 76.7 ± 3.8 a 78.9 ± 3.0 a 68.3 ± 5.5 a 2.1 0.15 51.7 ± 7.5 ab 50.6 ± 9.1 ab 33.3 ± 5.9 ab 1.9 0.17 10 85.6 ± 1.9 ABa 93.9 ± 1.8 Aa 85.0 ± 3. with the toxic agent and are kept protected (Arthur 2019). In contrast, progeny production for R. dominica, which is also an internal feeder, decreased with the increase of dose in all tested combinations of temperature and RH.…”
Section: Tablementioning
confidence: 86%
“…The reduction of offspring emergence is due to high adult mortality after 21 days of exposure. Furthermore, R. dominica females lay their eggs on the surface of kernels, where the larvae hatch, then bore, and finally enter the kernel to continue their development (Hill 2003;Edde 2012;Arthur 2019). Therefore, the newly hatched larvae will come in contact with the insecticide which eventually will kill them (Arthur 2016).…”
Section: Tablementioning
confidence: 99%